Autobiography workshop: narrativas de si e aprendizagem do inglês para o mundo de trabalho - Ogunjimi, Joseph Tolulope (2020)
English is used as the official or semi-official language in more than 60 countries and occupies an important position in another 20. It is dominant or firmly established, on six (6) continents. It is currently a requirement for international scientific communication (books, journals, academic conferences in the humanities and social sciences, technology, medicine, etc.), for international relations (diplomatic, trade, international sports competitions) and interpersonal. Encroaching everyday life (internet use, music, advertising and so on), which leads many professionals to want to learn English. As an English teacher, we observed that professionals acknowledge this need, many of them dropped out of English classes. This research aims to examine the proposal of Autobiography Workshop (AW) as a pedagogical device for learning English in the labor market. AW is characterized by the use of autobiographical narratives connected to situations and interactions experienced by professionals (interviews, self-presentations, conferences, etc.). We base our study on the following questions: To what extent do self-narratives stimulate professional interest in learning English? What are the potentialities and eventual limitations of the Autobiography Workshop? The research methodology focuses on the different stages of AW. Analyzes are based on episodic interviews (FLICK, 1997) with participants about AW, field notes in the researcher's Diary, and students' reactions and assessments of the pedagogical device used. The results of the research are still being analyzed.